Oil prices and gold prices on housing market in China: novel findings from the bootstrap approach - Ali, Mumtaz; Samour, Ahmed; Joof, Foday; Tursoy, Turgut (Emerald Group Publishing Ltd, 2024)
PurposeThis study aims to assess how real income, oil prices and gold prices affect housing prices in China from 2010 to 2021. Design/methodology/approachThis study uses a novel bootstrap autoregressive distributed lag (ARDL) testing to empirically analyze the short and long links among the tested variables. FindingsThe ARDL estimations demonstrate a positive impact of oil price shocks and real income on housing market prices in both the phrases of the short and long run. Furthermore, the results reveal that gold price shocks negatively affect housing prices both in the short and long run. The result can be attributed to China's housing market and advanced infrastructure, resulting in a drop in housing prices as gold prices increase. Additionally, the prediction of housing market prices will provide a base and direction for housing market investors to forecast housing prices and avoid losses. Originality/valueTo the best of the authors' knowledge, this is the first attempt to analyze the effect of gold price shocks on housing market prices in China.
Keywords: China; Oil prices; Gold prices; Bootstrap-ARDL; Real estate sector